2020
DOI: 10.1101/2020.08.20.259879
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Offline Memory Reactivation Promotes the Consolidation Of Spatially Unbiased Long-Term Cognitive Maps

Abstract: Spatial memories which can last a lifetime are thought to be encoded during 'online' periods of exploration and subsequently consolidated into stable cognitive maps through their 'offline' reactivation. However, the mechanisms and computational principles by which offline reactivation stabilize long-lasting spatial representations remain poorly understood. Here we employed simultaneous fast calcium imaging and electrophysiology to track hippocampal place cells over weeks of online spatial reward learning behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…To examine how these changes in firing altered interactions between neurons, we next calculated pairwise correlations of the normalized peri-SWRs firing rate curve of each neuron for each session in the two groups. Following spatial experience a more structured and clustered pattern emerged in the controls during the Post-CNO compared to the Pre-CNO sessions, consistent with previous data finding experience-dependent changes in coordinated activity(Grosmark and Buzsaki, 2016; Grosmark, 2020; Wilson and McNaughton, 1994) ( Fig. 2c; Extended Data Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…To examine how these changes in firing altered interactions between neurons, we next calculated pairwise correlations of the normalized peri-SWRs firing rate curve of each neuron for each session in the two groups. Following spatial experience a more structured and clustered pattern emerged in the controls during the Post-CNO compared to the Pre-CNO sessions, consistent with previous data finding experience-dependent changes in coordinated activity(Grosmark and Buzsaki, 2016; Grosmark, 2020; Wilson and McNaughton, 1994) ( Fig. 2c; Extended Data Fig.…”
Section: Resultssupporting
confidence: 90%
“…We first examined SWRs in each CA region independently (intra-region), comparing how their properties changed between the first rest session and the last rest session of the day. It has been suggested that spatial experience can lead to increases in SWR power, length and occurrence in subsequent rest sessions (Eschenko et al, 2008; Grosmark and Buzsaki, 2016; Grosmark, 2020; Ramadan et al, 2009); consistent with this, the normalized change in CA1 ripple-band power between the Pre- and Post-CNO sessions increased in control mice, but not in the DREADD mice. However, SWR frequency, duration, and occurrence were similar in both groups across the sessions ( Fig.…”
Section: Resultssupporting
confidence: 53%
“…To calculate a measure for spatial information content for granule cells in Fig. 1g, we adapted a traditional method of spatial information assessment 23,38,57 to Ca 2+ imaging data. For each cell, we used the firing rate-by-position vector and shuffled null distribution computed above and calculated the spatial information content for each as described previously 38,57 .…”
Section: Methodsmentioning
confidence: 99%
“…1g, we adapted a traditional method of spatial information assessment 23,38,57 to Ca 2+ imaging data. For each cell, we used the firing rate-by-position vector and shuffled null distribution computed above and calculated the spatial information content for each as described previously 38,57 . To account for the fact that low firing rates artificially produce high spatial information scores, we subtracted the mean of the shuffled information per spike from observed information per spike, divided by the standard deviation of the shuffled values to determine the spatial variance for each cell.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, numeours studies show that replay during retention or in spontaneous activities mediates sequence memory, structure representation, and novel inference, or in a broad sense, forms cognitive maps [59][60][61][62] . How to reconcile 1-D replay with 2-D neural geometry?…”
Section: Discussionmentioning
confidence: 99%